1, 7‐isoxazolyl Substituted BODIPY Dyes – Synthesis and Photophysical Properties. Issue 5 (1st February 2023) - Matveeva, Maria D.; Zheleznova, Tatyana Yu.; Kostyuchenko, Anastasia S.; Miftyakhova, Almira R.; Zhilyaev, Dmitry I.; Voskressensky, Leonid G.; Talarico, Giovanni; Efimov, Ilya V.
Abstract: A range of novel BODIPYs with the isoxazolyl groups at 1, 7‐positions were prepared from 3‐(4‐chlorophenyl)‐5‐(5‐phenyl‐1H‐pyrrol‐3‐yl)isoxazole and their photophysical properties were characterized. The presence of the isoxazolyl groups at 1, 7‐positions, shifts long‐wavelength absorption at 581±4 nm and emission at 622±3 nm in the near‐infrared region. A comparison of three variants of substituents at positions 1, 7 of BODIPY core is shown. Abstract : The synthesis of new isoxazole BODIPY derivatives and their photophysical properties are presented. Spectral investigations showed absorption maxima at 581±4 nm and emission at 622±3 nm of the obtained compounds. The presence of isoxazole groups at positions 1, 7 of BODIPY core has a greater effect on the shift of long wavelength absorption and emission in the near‐infrared region compared to aroyl substituents, but less in the comparison with analogs with oxadiazole groups.